2017
DOI: 10.3892/etm.2017.5503
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of histatin 1 against ultraviolet‑induced damage to human corneal epithelial cells

Abstract: The aim of the present study was to investigate the role of histatin 1 (Hst1) in human corneal epithelial cells (HCECs) exposed to ultraviolet (UV) radiation. Prior to UV irradiation for various durations, HCECs were pre-treated with different concentrations of Hst1 and the effect on cell apoptosis and cell viability were examined by flow cytometry, alamarBlue® and MTT assays to determine the optimal concentration of Hst1 and UV dose. Cells were then subjected to quantitative PCR, ELISA and western blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…From the above described results it may be deducted that the absence of amino sequences 1-11 in Hst2 and 23-38 in Hst5 (compared to Hst1) dramatically compromised their uptake rates. Consequently, we assessed the uptake dynamics and subcellular targets of truncated variants, F-Hst1 1-11 , F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] to explore their role in the cellular uptake of Hst1, Hst2 and Hst5. CLSM images revealed that the uptake of the truncated variants F-Hst1 1-11 , F-Hst1 12-22 and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] was much lower than that of the whole molecule F-Hst1 ( Figure 7A-D).…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
See 4 more Smart Citations
“…From the above described results it may be deducted that the absence of amino sequences 1-11 in Hst2 and 23-38 in Hst5 (compared to Hst1) dramatically compromised their uptake rates. Consequently, we assessed the uptake dynamics and subcellular targets of truncated variants, F-Hst1 1-11 , F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] to explore their role in the cellular uptake of Hst1, Hst2 and Hst5. CLSM images revealed that the uptake of the truncated variants F-Hst1 1-11 , F-Hst1 12-22 and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] was much lower than that of the whole molecule F-Hst1 ( Figure 7A-D).…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
“…At 60 min post-incubation Hst1 showed a mean fluorescence of 2.00 ± 0.15 × 10 6 AFU, which was significantly higher than that of F-Hst1 12-22 (0.25 ± 0.03 × 10 6 AFU), F-Hst1 1-11 (0.07 ± 0.00 × 10 6 AFU) and F-Hst1 23-38 (0.07 ± 0.00 × 10 6 AFU) ( Figure 7F). F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] mainly co-localized with the lysosomal marker (P coloc value of 0.55 ± 0.12, not with markers for the mitochondria or the ER or Golgi (Figure 8). Figure 7.…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
See 3 more Smart Citations